In vitro toxicity of epigallocatechin gallate in rat liver mitochondria and hepatocytes - Kucera, Otto; Mezera, Vojtech; Moravcova, Alena; Endlicher, Rene; Lotkova, Halka; Drahota, Zdenek; Cervinkova, Zuzana (Oxidative medicine and cellular longevity, 2015)
Epigallocatechin-3-gallate (EGCG) is the main compound of green tea with well-described antioxidant, anti-inflammatory, and tumor-suppressing properties. However, EGCG at high doses was reported to cause liver injury. In this study, we evaluated the effect of EGCG on primary culture of rat hepatocytes and on rat liver mitochondria in permeabilized hepatocytes. The 24-hour incubation with EGCG in concentrations of 10 μmol/L and higher led to signs of cellular injury and to a decrease in hepatocyte functions. The effect of EGCG on the formation of reactive oxygen species (ROS) was biphasic. While low doses of EGCG decreased ROS production, the highest tested dose induced a significant increase in ROS formation. Furthermore, we observed a decline in mitochondrial membrane potential in cells exposed to EGCG when compared to control cells. In permeabilized hepatocytes, EGCG caused damage of the outer mitochondrial membrane and an uncoupling of oxidative phosphorylation. EGCG in concentrations lower than 10 μmol/L was recognized as safe for hepatocytes in vitro.
Keywords: hepatocyty; viabilita buněk; Male; Caspase 3; Rats, Wistar; kaspasa 3; Tumor Necrosis Factor-alpha; reaktivní formy kyslíku; fluorescenční mikroskopie; Oxidative Phosphorylation; Mitochondria, Liver; Cell Survival; mužské pohlaví; potkani Wistar; Hepatocytes; krysa rodu Rattus; Reactive Oxygen Species; kultivované buňky; jaterní mitochondrie; Animals; Microscopy, Fluorescence; Tea; zvířata; Rats; Catechin; TNF-alfa; čaj; membránový potenciál mitochondrií; Cells, Cultured; katechin; oxidativní fosforylace; Membrane Potential, Mitochondrial